(3GdeSJWQa ef cd af eSJXQas - (3LeGd GdOjf eMeO Hf CMeO GdNWjH GdGHTjgjs ((3GdLGeY GdeXaQ s)
(3ChdgG (B:s
(3CeG HYO , abO QCjJ LeGYI ef Phi Gdage LeYhG CTjGA cKjQI ef GdBOGH hGdMce, hHSWhG eLdOGJ ef GdJhGQjN hGdfhGOQ hSejJg GdeSJWQa ef cd af eSJXQa s
(3BNQgG (B:s
(3RaGdLhGH Yf Pdc Cf GdSQGL CYe ef GdbeQ , dCf GdSQGL GdeQGO Hg GdTeSbGd Gddg JYGdi (B:(3hLYd GdTeS SQGLkG hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs